Bezout Rings of Stable Range 1.5 - Shchedrik, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
A ring R has a stable range 1.5 if, for every triple of left relatively prime nonzero elements a, b and c in R, there exists r such that the elements a+br and c are left relatively prime. Let R be a commutative Bezout domain. We prove that the matrix ring M_2 (R) has the stable range 1.5 if and only if the ring R has the same stable range.